The Impact of the exchange rate unification on trade balance in Myanmar - WIN, Zar Kyi (KDI School, 2016)
This study analyzes the impacts of the exchange rate unification on the trade balance in Myanmar based on Autoregressive Distributed Lag (ARDL) Model. This paper’s main objective is to determine whether the exchange rate has positive or negative effects on the trade balance. This study has discovered that the exchange rate unification has a positive effect on the trade balance in the long run. Additionally, this study finds that Exchange Rate and Foreign Direct Investment have positive effects on the trade balance while GDP growth rate and Inflation has negative impact in the long run. As a policy implication, this study suggests that the government should focus on economic stability and effective monetary policies within the country. Moreover, Myanmar’s new exchange rate system should align with the market speculators without priority of either exporters or importers.
Thesis(Master) --KDI School:Master of Public Policy,2016